A Case of Autoimmune Neutropenia in a Patient Undergoing Breast Cancer Surgery - Mio Adachi; Goshi Oda; Masatake Hara; Yuichi Kumaki; Tomoyuki Fujioka; Toshiyuki Ishiba; Ukihide Tateishi (Case Reports in Surgery)
Autoimmune neutropenia (AIN) is an extremely rare condition, and there is no effective treatment option for this disorder. AIN can cause major complications in patients with perioperative infection. Herein, we present a 56-year-old female patient who was scheduled for breast cancer surgery. However, she was unexpectedly diagnosed with AIN. Thus, the surgery was postponed, and endocrine therapy was started. After 7 months of treatment, the surgery was performed. Granulocyte colony-stimulating factor was administered before the surgery, but the patient’s neutrophil count did not increase. Thus, levofloxacin was administered during the surgery. The patient had fever (38.6°C) 1 day after the surgery. Her surgical wound did not present with redness, and there were no other signs of infection. The fever subsided on the second day after the surgery. Nevertheless, antibiotics were administered for 5 days. The patient was discharged on the sixth day after the surgery.